Bioactive profile and anti-UV activities of ethyl acetate extract of Rhizophora apiculata leaves - Irwan, Irwan; Aly, Maghsal; Rusydi, Ichsan; Nurliza, Eli; Nursafiah, Nursafiah; Akram, Habibul (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Mangroves plants such as Rhizophora apiculata are known to possess a diverse array of bioactive compounds with antioxidant and photoprotective properties. This study aimed to evaluate the anti-UV activity and bioactive composition of the ethyl acetate extract of R. apiculata leaves. The extraction was performed using the maceration method over 3 24 hours with ethyl acetate as the solvent. UV absorption was assessed using UV-Visible spectrophotometry, while compound identification was carried out through Gas ChromatographyMass Spectrometry (GC-MS). The extract exhibited significant UV absorption in the 290320 nm range, with Sun Protection Factor (SPF) values ranging from 2.5300.03 (low protection) to 37.0800.47 (high protection), indicating strong potential as a natural sunscreen agent. GC-MS analysis revealed several bioactive constituents, including lupeol, friedelan-3-one, cyclohexane-1,3,5-triphenyl, -tocopherol, and 1,3,5,7-cyclooctatetraenecompounds recognized for their UV-absorbing and antioxidant activities. The synergistic action of these phytochemicals is believed to contribute to the extracts overall photoprotective efficacy.Keywords:Rhizophora apiculataBioactive compoundsAnti-UVExtractEthyl Acetate